Financing Infrastructure for New Economies in the Context of Dislocated Markets - Zeph Nhleko (The Thinker)
Financing Infrastructurefor New Economies in the Context of Dislocated MarketsIntroductionOne could be forgiven for thinking that given the close to 20 deadly pandemics (LePan, 2020) and over 70 economic crises humanity has seen since the first century, we should by now know how mutation works and what economic outcomes to expect. This view is influenced by the established understanding that irrespective of the type of crisis – natural, financial, economic or otherwise – all crises have some similarities (Reinhart and Rogoff, 2011). For example, we can anticipate varying impacts f rom crises on risk appetite in markets, liquidity, productivity, trade, economic activity, standard of living – sometimes even lives and fiscal debt.